KETERLIBATAN ORANG TUA DALAM PEMBELAJARAN DARING DI TAMAN KANAK-KANAK AN-NUR KECAMATAN GLENMORE KABUPATEN BANYUWANGI - Yuli Tri Andini (JURALIANSI: Jurnal Lingkup Anak Usia Dini, 2022)
A Learning in Kindergarten experiences a shift in habits. Previously, learning was carried out in schools with the guidance of classroom teachers. At this time, the government announced the existence of WFH (Work From Home) as a new challenge for parents to participate as teachers in carrying out school learning programs. The research method uses study literacy by using various sources of literature review from several previous studies that are relevant based on the topic of the problem. The results showed that parental involvement plays an important role in the implementation of learning, parents collaborate with teachers so that learning objectives are optimal. Children's learning motivation increases along with the close cooperation between children and parents. There are several obstacles, namely the limitations of parents in using technology, busy working parents, and network disturbances and internet quotas that are charged to parents. Even though parents show an attitude of self-sacrifice in carrying out their obligations to meet their children's educational needs, so that it continues to run well.